PENURUNAN KADAR FOSFAT LIMBAH CAIR USAHA LAUNDRY DENGAN KARBON AKTIF SEKAM PADI - Rahmi Garmini; Zairinayati Zairinayati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Laundry business is a business that can produce liquid waste originating from detergents containing several chemicals or chemicals such as phosphate (70-80%), surfactant (20-30%), ammonia, nitrogen, dissolved solids, turbidity, BOD (Biochemical Oxygen Demand), and COD (Chemical Oxygen Demand). Laundry wastewater containing phosphate compounds will cause Eutrophication. The purpose of this study was to determine the effectiveness of the use of rice husk activated carbon in reducing phosphate levels in laundry business wastewater. This research is an experimental study (Experimental Research) with 3 repetitions and treated with doses of 3 grams, 4 grams, 5 grams of activated carbon of rice husk, each of which was added to 330 ml of laundry wastewater. From the results of the Anova test data analysis, it was found that the P value was 0.110> 0.05, meaning that there was no effect of giving rice husk activated carbon in reducing phosphate levels in the laundry business.